[OA171] PET-TC post therapy dosimetry in radioembolization with resin 90Y microspheres: Comparison with pre treatment SPECT-TC 99mTc-MAA results. (August 2018) - Richetta, Elisa; Cutaia, Claudia; Poli, Matteo; Pasquino, Massimo; Tabone, Marco; Paradisi, Benedetta Peiretti; Pacilio, Massimiliano; Lanconelli, Nicola; Pellerito, Riccardo Emanuele; Stasi, Michele
Abstract : Purpose: 90 Y PET-CT can be acquired after 99 Y-resin microsphere radioembolization to describe radioactivity distribution. Aim of this study was to compare post-therapy dosimetry performed on 90 Y PET-CT images with SPECT-TC 99m Tc-MAA pre-therapy dose results. Methods: SPECT-TC 99m Tc-MAA acquisition was performed on 10 HCC patients before radioembolization. Doses to tumour (T) and normal liver (NL) were calculated form SPECT-TC images (Iterative Flash3D, voxel4.8 mm, attenuation and scatter corrected) with partition model (MIRD) and 3D voxel method (relative calibration, local deposition with 90 Y voxel S-values) as well. After the therapeutic administration, PET-TC images were acquired using the low branch ratio positron emission (TOF, OSEM3D, voxel 4 mm, attenuation and scatter corrected, scan-time 20 min/bed). With the same dosimetric methods mean doses and DVHs curves were obtained on post therapy images and compared to pre therapy ones [ Δ % = (dose POST-dose PRE)/dose POST]. Results: 90 Y resin microspheres were administered to 10 patients (7 M, 3F). Mean activity was 1.65 ± 0.75 GBq (range 0.8 ÷ 2.5 GBq). T volumes (105 ± 111 ml, 20 ÷ 231 ml) and NL volumes (627 ± 518 ml, 307 ÷ 1224 ml) showed high variations. MIRD mean tumour doses from 99m Tc SPECT-TC were lower than those from 90 Y PET-TC (184.1 ± 40.6 Gy vs 202.1 ± 68.1 Gy, max Δ % 0.30, correlation r = 0.62). MIRD mean absorbed doses to NL from 99m Tc-MAA SPECT-CT was instead greater than those from PET-CT (59.5 ± 22.4 Gy vs. 53.3 ± 13.9 Gy, max Δ % −0.44, r = 0.74). Similar results were obtained with voxel doses for NL (SPECT-TC 47.5 ± 14.8 Gy vs PET-TC 31.8 ± 7.9 Gy, max Δ % −0.39, r = 0.75), while for voxel T doses 99m Tc SPECT-TC were in mean higher than those from 90 Y PET-CT (153.7 ± 37.9 Gy vs. 111.7 ± 21.8 Gy, max Δ % −0.39 %, r = 0.61). The underestimation of recovered activity on 90 Y PET-CT images, pointed out by some authors on phantom acquisition, could affect high uptake regions when dosimetry evaluation is performed at voxel level. DVHs curves comparison showed controversial results requiring further investigations. Conclusions: Post-SIRT dosimetry based on 90 Y-microsphere PET-CT is effective and correlates with SPECT-CT 99m Tc-MAA pre-therapy results.